1900 Vt. Acts and Resolves 210, No. 178, § 10, pt. 15. - (:unkn) unknown (My University, 1900)
To regulate and restrain the use and sale of rockets, squibs, fire-crackers, toy pistols, or other fire-works within the village, also guns, cannon and explosives.
Keywords: DISCHARGE